Aphid parasitoids (Hymenoptera, Braconidae, Aphidiinae) and their associations related to biological control in Brazil - Starý,Petr (2007)
This study evaluated the parasitoid-aphid-plant associations in Brazil with the objective of developing a useful research database for further studies of aphid parasitoid ecology and aphid management. The original material was obtained from collections made in Paraná, Rio Grande do Sul, Minas Gerais, and São Paulo states. The published information on the Aphidiinae in Brazil is revised. The general features of the target parasitoid fauna of Central and South America is summarized and promising biological control programs of some aphid species in Brazil is discussed.